Pengaruh Strategi Pemasaran, Kualitas Produk dan Harga Jual Terhadap Keputusan Pembelian Produk Bahan Bangunan (Studi Kasus PT. Homesmart Medan) - Ferdi Isvano; Taufiq Risal (Universitas Katolik Widya Karya Malang, 2023)
The aim of this research is to determine the influence of marketing strategy, product quality and selling price on purchasing decisions for building material products (case study of PT. Homesmart Medan). The type of research used in this research uses quantitative research. Data collection techniques used in this research include interviews, observation and questionnaires. The testing methods used in this research use exploratory instrument tests, descriptive statistical tests, classical hypothesis tests, multiple linear regression tests, and hypothesis tests. The results of this research hypothesis are that the marketing strategy variable does not have a positive and significant effect on purchasing decisions, while the product quality and selling price variables have a positive and significant effect on purchasing decisions. However, it was found that the decision to purchase construction products was influenced by marketing strategy variables, product quality and selling price (case study of PT. Homesmart Medan). ​